Pengaruh Cashback, Flash Sale, Dan Kemudahan Penggunaan Aplikasi Terhadap Keputusan Pembelian Pada Shopee (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2020) - Rahma, Vina Maulidya; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study was conducted to determine and analyze the influence of Cashback, Flash Sale, and Ease of Use of the Application on Purchase Decisions partially on Shopee. The population in this study were students of the Faculty of Economics and Business, Universitas Islam Malang, Class of 2020 who had used the Shopee Application. The approach method used a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to 85 respondents and using the SPSS analysis tool. The results of the study showed that cashback, flash sale, and ease of use of the application simultaneously had a significant effect on purchase decisions on Shopee by students of the Faculty of Economics and Business, Unisma, class of 2020. The cashback and flash sale variables partially had a significant effect on purchase decisions on Shopee by students of the Faculty of Economics and Business, Unisma, class of 2020. The ease of use of the application variable partially did not have a significant effect on purchase decisions on Shopee by students of the Faculty of Economics and Business, Unisma, class of 2020. Keywords: Cashback, Flash Sale, Ease of Use of the Application, Purchase Decision